Effect of plyometric vs. dynamic weight training on the energy cost of running - Berryman, N.; Maurel, D.; Bosquet, L. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study is to compare the effects of 2 strength training methods on the energy cost of running (Cr). Thirty-five moderately to well-trained male endurance runners were randomly assigned to either a control group (C) or 2 intervention groups. All groups performed the same endurance-training program during an 8-week period. Intervention groups added a weekly strength training session designed to improve neuromuscular qualities. Sessions were matched for volume and intensity using either plyometric training (PT) or purely concentric contractions with added weight (dynamic weight training [DWT]). We found an interaction between time and group (p < 0.05) and an effect of time (p < 0.01) for Cr. Plyometric training induced a larger decrease of Cr (218 ± 16 to 203 ± 13 ml/kg·km) than DWT (207 ± 15 to 199 ± 12 ml/kg·km), whereas it remained unchanged in C. Pre-post changes in Cr were correlated with initial Cr (r = -0.57, p < 0.05). Peak vertical jump height (VJHpeak) increased significantly (p < 0.01) for both experimental groups (DWT = 33.4 ± 6.2 to 34.9 ± 6.1 cm, PT = 33.3 ± 4.0 to 35.3 ± 3.6 cm) but not for C. All groups showed improvements (p < 0.05) in Perf3000 (C = 711 ± 107 to 690 ± 109 seconds, DWT = 755 ± 87 to 724 ± 77 seconds, PT = 748 ± 81 to 712 ± 76 seconds). Plyometric training were more effective than DWT in improving Cr in moderately to well-trained male endurance runners showing that athletes and coaches should include explosive strength training in their practices with a particular attention on plyometric exercises. Future research is needed to establish the origin of this adaptation.